Effect of G‐Coat Plus on the mechanical properties of glass‐ionomer cements. (December 2013) - Bagheri, R; Taha, NA; Azar, MR; Burrow, MF
Abstract Background Although various mechanical properties of tooth‐coloured materials have been described, little data have been published on the effect of ageing and G‐Coat Plus on the hardness and strength of the glass‐ionomer cements (GICs). Methods Specimens were prepared from one polyacid‐modified resin composite (PAMRC; Freedom, SDI), one resin‐modified glass‐ionomer cement; (RM‐GIC; Fuji II LC, GC), and one conventional glass‐ionomer cement; (GIC; Fuji IX, GC). GIC and RM‐GIC were tested both with and without applying G‐Coat Plus (GC). Specimens were conditioned in 37 °C distilled water for either 24 hours, four and eight weeks. Half the specimens were subjected to a shear punch test using a universal testing machine; the remaining half was subjected to Vickers Hardness test. Results Data analysis showed that the hardness and shear punch values were material dependent. The hardness and shear punch of the PAMRC was the highest and GIC the lowest. Applying the G‐Coat Plus was associated with a significant decrease in the hardness of the materials but increase in the shear punch strength after four and eight weeks. Conclusions The mechanical properties of the restorative materials were affected by applying G‐Coat Plus and distilled water immersion over time. The PAMRC was significantly stronger and harder than the RM‐GIC or GIC.